2011
DOI: 10.1021/jo2019174
|View full text |Cite
|
Sign up to set email alerts
|

Glycosidation of Thioglycosides in the Presence of Bromine: Mechanism, Reactivity, and Stereoselectivity

Abstract: Elaborating on previous studies by Lemieux for highly reactive "armed" bromides, we discovered that β-bromide of the superdisarmed (2-O-benzyl-3,4,6-tri-O-benzoyl) series can be directly obtained from the thioglycoside precursor. When this bromide is glycosidated, α-glycosides form exclusively; however, the yields of such transformations may be low due to the competing anomerization into α-bromide that is totally unreactive under the established reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 52 publications
2
76
0
Order By: Relevance
“…33 A series of reactions between perbenzylated bromides with glycosyl acceptor 4 34 was performed as depicted in Table 1 (entries 1–3). First, a reaction of bromide 2 with acceptor 4 was performed in the presence of TMSOTf (0.08 equiv) as the activator and Ag 2 O (3.0 equiv) as the HBr scavenger.…”
Section: Resultsmentioning
confidence: 99%
“…33 A series of reactions between perbenzylated bromides with glycosyl acceptor 4 34 was performed as depicted in Table 1 (entries 1–3). First, a reaction of bromide 2 with acceptor 4 was performed in the presence of TMSOTf (0.08 equiv) as the activator and Ag 2 O (3.0 equiv) as the HBr scavenger.…”
Section: Resultsmentioning
confidence: 99%
“…In an effort to obtain more complex oligosaccharide sequences, Takahashi adapted another instrument, Liquid Crystal on Silicon (L-COS) by Moritex, which was used to make a dimeric Le x (48) and its analogs. Using this instrument, Takahashi et al achieved automation of stirring, temperature control, and rate of reagent addition for each glycosylation and deprotection step shown in Fig.…”
Section: Automation Of the One-pot Oligosaccharide Synthesis In Solutionmentioning
confidence: 99%
“…Finally, the remaining 3′-OH of the resulting hexasaccharide intermediate was fucosylated by the addition of a donor (47) and NIS/TfOH. Resultantly, the desired heptasaccharide (48) was obtained in eight hours in 24% yield (average 79% yield per step). The automated synthesizer could be combined with Combi Flash automated column chromatograph, which was used for purification of the resulting oligosaccharides.…”
Section: Automation Of the One-pot Oligosaccharide Synthesis In Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation and characterisation of glycosyl bromides using in situ NMR analysis has previously been described by Demchenko and co-workers. 30 Formation of the glycosyl bromide was carried out in CDCl 3 in a standard NMR tube equipped with a septum and immersed in liquid nitrogen (−196°C). NMR analysis demonstrated that full conversion of the thioglycoside to the bromide 4 was complete within five minutes and that no disaccharide formation or anomerisation was observed even upon warming of the glycosyl bromide to room temperature (Fig.…”
Section: Organic and Biomolecular Chemistry Papermentioning
confidence: 99%